Conversion, circumcision, and ritual murder in medieval Europe - Tartakoff, Paola (The Middle Ages Series, 2020)
Frontmatter -- Contents -- Note on Usage -- Introduction -- Chapter 1. Christian Vulnerabilities -- Chapter 2. From Circumcision to Ritual Murder -- Chapter 3. Christian Conversion to Judaism -- Chapter 4. Return to Judaism -- Chapter 5. Contested Children -- Conclusion -- List of Abbreviations -- Notes -- Bibliography -- Index -- Acknowledgments